Distribution of Phosphate Solubilizing Bacteria and Soil Phosphatase Activity in Different Land Uses - M. R. Sarikhani; N. Chalabianlu; S. S. Alavikia (مجله آب و خاک, 2016)
Introduction: Phosphorous is one of the essential macronutrients for plant growth and development but its mobility in soil is very low. The utilization of the soil biological potential, in particular phosphate solubilizing bacteria, is an efficient way which can be used for exploiting available sources of phosphorous in the soil. The principal mechanism for mineral phosphate solubilization is the production of organic acid, and acid and alkaline phosphatases play a major role in the mineralization of organic phosphorous in the soil. Presence and distribution of phosphate solubilizing bacteria in the soil and soil phosphatase activities is influenced by soil conditions such as climate, soil type, vegetation and land uses. In order to understand the relationships and considering the importance of the subject, the soil samples were chosen from two different climates; semi-moist (Fandoghlou-Ardabil) and semi-arid (Namin- Ardabil) under culture of legumes, cereals and uncultivated areas, in this experiment. Materials and Methods: In order to study the effects of different land uses, climate conditions and soil physicochemical properties on phosphate solubilizing microorganism (PSM) distribiution and soil acid and alkaline phosphatase activity, a factorial experiment based on completely randomized design was performed with considering three different land uses (including legumes, cereals and wasteland) and two climate conditions (semi-moist: Fandoghlu- Ardabil and semi-arid: Namin-Ardabil). Four composite soil samples (0-25 cm) were taken from each land uses. Finally, a total number of 24 soil samples were used to enumerate phosphate solubilizng bacteria and evaluate soil phosphatase activities. The enumeration and selection of bacteria in the mineral Sperber medium was done by attention to the clear zone production in the presence of tri-calcium phosphate and in organic sperber (IHP+BCIP) due to blue phenotype of grown colonies. Also, phosphatase activity of soil samples was assessed based on the usual methods for phosphatase assessment. Moreover, after the evaluation of the physicochemical properties of the soil samples and soil enzyme activities and PSB distribution, all data were analyzed by SPSS and MSTAT-C softwares. Results and Discussion: The Sperber mediums containing mineral and organic phosphates were used in counting the number of PSB. According to the results, the highest total number of bacteria (>6 log cfu/g) was gained in legume land uses in both climate conditions. Furthermore, the highest numbers of organic and mineral phosphate solubilizing bacteria (5.3 log cfu/g) were counted in samples taken from pastures, in other word in soil samples which were collected from uncultured land in semi-moist climate conditions. Enzyme assay showed that acid phosphatase activity (430 µg pNP/g.h) in semi-moist climate conditions were increased three times in comparison to semi-arid climate conditions. Perhaps, this increase can be explained by parameters such as high moisture content and organic matter which can cause an increase in the number of bacteria and soil enzyme content. Our results showed that, alkaline phosphatase activities (APAs) were affectd by interaction effects of land uses and climate, wherein the highest APA (810 µg pNP/g.h) was measured in legume samples in semi-arid climate conditions. The pH of these soil samples and supporting legume rhizospheres from AP producing microorganisms may be the reasons of this increment. Conclusion: The highest activity of the soil acid phosphatase was observed in soil samples which were taken from uncultivated area under semi-moist climate conditions (namely pastures) (866.59 µgPNP/g.h) while the soil alkaline phosphatase activity had high mean in legume land use soil samples under semi-arid climate conditions (795.15 µPNP/g.h). The total number of bacteria was the highest in semi-arid leguminous land use (14.13×106 cfu/g) but the total numbers of solubilizing bacteria in both mineral and organic media were the highest in semi-moist uncultivated area (respectively 1.9 ×106 and 1.48 × 106cfu/g).